Answer:
28.25
Step-by-step explanation:
Answer:
(3x)(x-2)(x-1)
Step-by-step explanation:
First we can factor out the 3x from each and are then left with x^2-3x+2. Now we can go ahead and factor. Looking for two variables that multiply to become positive 2 and add to become negative 3, we get negative 2 and negative 1. We now know that both (x-1) and (x-2) are factors. We now have all three factors and we can multiply to check if we get the right answer, and we do.
Answer:
C. (x + 2, Y - 3)
Step-by-step explanation:
C. (x + 2, Y - 3)
Answer:
29.3
Step-by-step explanation:
4x+12+5x+3x-4=360
Add the X's up & move the numbers w/out factors (X's) to the 360 side. This will look like 12x=352
Then, you divide each by 12, leaving you with x=29.3
Might be wrong, let me know and I will rework it.
Answer: hewo, there! your answer is below
x= -5/4
or x= 8
Step-by-step explanation:
step 1: Subtract 27x+40 from both sides.
4x2−(27x+40)=27x+40−(27x+40)
4x2−27x−40=0
Step 2: Factor left side of equation.
(4x+5)(x−8)=0
Step 3: Set factors equal to 0.
4x+5=0 or x−8=0
hope this helps you
have a great Day
Plz makr branilest